Using a Biomechanical Analysis Approach to the Accuracy of Shooting Throws in Petanque Sport: Literature Review - Boby Helmi; Taufiq Hidayah; Harry Pramono; Mugiyo Hartono; Tatang Iskandar (OVS LLC, 2024)
Study Purpose. The purpose of this study was to determine how biomechanical analysis can be used in petanque shooting techniques. Materials and methods. This review study followed the PRISMA standards for systematic reviews and meta-analyses. Studies had to be published within the previous five years, from January 2019 to July 2023. (1) shooting petanque; (2) biomechanical analysis were the keywords used in the search process. Scopus and the Science and Technology Index (SINTA) were used for study. Results. This review consists of nine studies. In five research articles, motion analysis was considered, which resulted in a discussion of the direction and angle of petanque throw biomechanics. Four research articles deal with the analysis of petanque shooting accuracy, leading to a discussion of angle, direction, arc, and focus. Conclusions. Biomechanical analysis helps to understand intensity, speed, and posture for better bidding, improved performance, and reduced risk of injury, while increasing speed and efficiency, preventing muscle imbalances, and achieving better technical positions in shooting petanque sports.